2024
DOI: 10.1186/s12888-023-05478-1
|View full text |Cite
|
Sign up to set email alerts
|

Causal relationships between atopic dermatitis and psychiatric disorders: a bidirectional two-sample Mendelian randomization study

Suqi Cao,
Zicheng Zhang,
Lei Liu
et al.

Abstract: Background Observational studies have suggested the potential associations between atopic dermatitis (AD) and psychiatric disorders. However, the causal relationship between them remains uncertain. This study aimed to evaluate the potential bidirectional causal relationship between AD and psychiatric disorders, including autism spectrum disorder (ASD), major depressive disorder (MDD), attention deficit hyperactivity disorder (ADHD), bipolar disorder (BD), anorexia nervosa (AN), Tourette syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Other studies have found that depression may increase the susceptibility of women to infertility ( 21 ). Furthermore, some studies have found that atopic dermatitis can increase the risk of autism spectrum disorder, suggesting a potential causal association between the two ( 22 ). However, to our knowledge, no MR studies exploring a genetic causal link between mental illness and TB have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found that depression may increase the susceptibility of women to infertility ( 21 ). Furthermore, some studies have found that atopic dermatitis can increase the risk of autism spectrum disorder, suggesting a potential causal association between the two ( 22 ). However, to our knowledge, no MR studies exploring a genetic causal link between mental illness and TB have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms range from mild to acute, and the prevalence of cognitive impairment differs depending on the age, level of education and geographical location [23]. Cao S. et al (2024) emphasized the significant causal association between AD and an increased risk of autism spectrum disorder and also identified bipolar disorder and anorexia nervosa as risk factors for atopic dermatitis [24]. Earlier reports have demonstrated a relationship between AD and psoriasis, and cognitive functions [25][26][27].…”
Section: Introductionmentioning
confidence: 99%